Seasonal Uptake of Nutrients by Chenin Blanc in Sand Culture: II. Phosphorus, Potassium, Calcium and Magnesium - Conradie, W. J. (South African Journal of Enology and Viticulture, 2017)
The seasonal uptake of phosphorus, potassium, calcium and magnesium as well as their distribution in the vine were determined for Chenin blanc/99R vines grown in sand culture under South African climatic conditions. Phosphorus absorption showed two distinct peaks-the first ranging from after bud burst until veraison, and the second, less prominent, from about five weeks after harvest into the leaf fall period. Potassium was absorbed from about three weeks after bud burst until four to five weeks after harvest. No potassium was absorbed during leaf fall. Active absorption of calcium started after bud burst and continued until veraison. A second, less pronounced absorption period occurred during the six weeks before leaf fall. Similarly, absorption of magnesium started after bud burst and continued until veraison, after which the absorption rate decreased and ceased with the onset of leaf fall. A significant amount of the phosphorus and potassium absorbed during the post harvest period was retained in the permanent parts of the vine. However, most of the post harvest calcium and magnesium gains were lost through leaf fall. Most of the calcium retained by the permanent parts of the vine, was stored in the bark. There was an apparent translocation of potassium from the leaves to the permanent structure of the vine during leaf fall. This was not noticeable for any of the other three nutrients.